2015
DOI: 10.4067/s0718-16202015000300011
|View full text |Cite
|
Sign up to set email alerts
|

Fire, logging and establishment patterns of second-growth forests in south-central Chile: implications for their management and restoration

Abstract: M.E. González, P. Szejner, P.J. Donoso, and C. Salas. 2015. Fire, logging and establishment patterns of second-growth forests in south-central Chile: implications for their management and restoration. Cien. Inv. Agr. 42(3): 427-441. Second-growth forests represent the greatest potential resource for forest management and large-scale ecological restoration in many regions. In south-central Chile, second-growth forests include those dominated by Nothofagus obliqua, N. dombeyi, Drimys winteri, and a mixture of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
(15 reference statements)
0
8
0
1
Order By: Relevance
“…However, their study does not cover plant mortality. Finally, González et al (2016) have shown that wildfires transform Chilean forests from primary to secondary forest, which may host a reduced biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…However, their study does not cover plant mortality. Finally, González et al (2016) have shown that wildfires transform Chilean forests from primary to secondary forest, which may host a reduced biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…The two Nothofagus-dominated secondary forests (NoSg and NdSg) can be considered in the "understory reinitiation" stage (sensu [48]), with larger trees and basal areas and lower tree densities, but still similar heterogeneity. The great differences among these two successional stages, as expressed in this study), are the result of differences in few decades since establishment, in growth rates of dominant species (Nothofagus species are among the fastest in Chile, [15,16,49,50]), and also in the type and magnitude of the disturbance that generated these forests [32], which, for example, determined the differences in species composition. In general, second-growth forests in the stem exclusion stage of stand development will have less commonalities with structural characteristics of old-growth forests than when comparing forests in the understory reinitiation stage of stand development with old-growth forests, but there may be exceptions, such as with dead wood.…”
Section: Causes and Patterns In The Differences Between Second And Olmentioning
confidence: 99%
“…The other three second-growth forests were dominated (i.e., at least 50% of the basal area in one species), respectively, by Drimys winteri (DwSg), Nothofagus dombeyi (NdSg), and Nothofagus obliqua (NoSg), but all were also mixtures and had common late-successional tree canopy species such as E. cordifolia, L. philippiana, A. punctatum and D. winteri (Table 1). The MESg and DwSg forests were mostly established between 1940 and 1970 (they were on average close to 60 years old), and NoSg and NdSg forests were mostly established between 1910 and 1940 (they were on average 90 years old; [32]). The remaining successional forest (NdM) was also dominated by N. dombeyi and was also originated by human-caused fires as observed in the field.…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dos de los bosques muestreados corresponden a bosques nativos secundarios en distintos estados sucesionales (temprano e intermedio) y uno a un bosque adulto (BA) en un avanzado estado sucesional. El bosque en un estado sucesional más temprano corresponde a un bosque secundario mixto siempreverde (BSMS) que fue originado por madereo y presumiblemente fuego a inicios de los años 30 del siglo veinte, y el bosque secundario dominado por N. dombeyi (BSNd) fue originado luego de un incendio severo que ocurrió cerca de 1914 (González et al 2015). Diversos atributos de composición y estructura de estos bosques son reportados en Ponce et al (2017).…”
unclassified